1982
DOI: 10.1136/jcp.35.8.866
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein concentration as a guide to antibiotic therapy in acute leukaemia.

Abstract: SUMMARY Serial monitoring of the serum C-reactive protein (CRP) concentration was performed, using a one-hour laser-immunonephelometric assay, during 29 episodes of infection in 22 neutropenic patients with acute leukaemia. Serum CRP increased to above a diagnostic level of 100 mg/l in all 29 episodes and continued to rise progressively until appropriate antibiotics, or granulocytes, were given when it fell with a half-life of approximately three days. Serial study of the serum concentration was of value in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 8 publications
1
28
0
1
Order By: Relevance
“…Levels of CRP rise in serum 6-8 h after organ injuries and reach the maximal levels within 48-72 h. Following the CRP levels during treatment of infection gives information about the status of disease at an early stage [12,13] . Nevertheless, due to the long half-life (8-21 h) [11][12][13][14] it might take more than 24 h before the levels rise or decrease at the beginning or after the effective treatment has been initiated. We could not fi nd a convincing advantage using HGF compared to CRP after 48-72 h of treatment in our previous study [6] , but we observed in this study that HGF was signifi cantly better than CRP in the identifi cation of nonresponders after only 24 h of treatment ( table 1 , fi g. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of CRP rise in serum 6-8 h after organ injuries and reach the maximal levels within 48-72 h. Following the CRP levels during treatment of infection gives information about the status of disease at an early stage [12,13] . Nevertheless, due to the long half-life (8-21 h) [11][12][13][14] it might take more than 24 h before the levels rise or decrease at the beginning or after the effective treatment has been initiated. We could not fi nd a convincing advantage using HGF compared to CRP after 48-72 h of treatment in our previous study [6] , but we observed in this study that HGF was signifi cantly better than CRP in the identifi cation of nonresponders after only 24 h of treatment ( table 1 , fi g. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Although some 30 plasma proteins show acute phase behaviour, 18 they differ considerably in the rate of their response and incremental increase in plasma concentration. The criteria for a reliable marker of the acute phase response are: rapid and substantial increase in concentration following an inflammatory stimulus, and a short half-life WBC, CRP and AGP on day 6.…”
Section: Discussionmentioning
confidence: 99%
“…A complicating factor in the immunosuppressed child is the difficulty of diagnosing an infection [3,6,8,9]. Fever is not a valuable sign, since many non-infectious processes may result in fever [6].…”
Section: Introductionmentioning
confidence: 98%
“…Bone marrow depression is an unavoidable consequence of aggressive therapy and infections and suspicion of infection are perhaps the most common problems in an oncology ward. Rapid therapy with broad spectrum antibiotics has resuited in a significant improvement and reduction in early mortality, but infections still remain the main cause of morbidity and mortality during induction therapy [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation